Quantitative analysis of pharmacokinetic profiles of verapamil and drug–drug interactions induced by a CYP inhibitor using a stable isotope-labeled compound. Issue 6 (December 2016) - Kataoka, Makoto; Kojima, Chie; Ueda, Kazuki; Minami, Keiko; Higashino, Haruki; Sakuma, Shinji; Togashi, Kazutaka; Mutaguchi, Kuninori; Yamashita, Shinji
Abstract: The purpose of the present study is to demonstrate a useful approach (isotope-IV method) for analyzing drug–drug interactions (DDIs) following the oral administration of drugs using stable isotope-labeled compounds. Verapamil hydrochloride (VER) was used as a drug model. Deuterium-labeled VER (VER-d6, 0.005 mg/kg) was intravenously administered to rats with or without a pre-treatment with 1-aminobenzotriazole (ABT, 100 mg/kg), a potent CYP inhibitor, 1.5 h after the oral administration of VER (1 mg/kg). PK parameters such as AUCpo, AUCiv, and CLtot were evaluated after the oral and intravenous administration of VER from the plasma concentration-time profiles of VER and VER-d6 in each rat. The oral bioavailability (F) of VER in rats was calculated as 0.02 ± 0.01 and was significantly increased to 0.45 ± 0.24 by the pre-treatment with ABT. Further PK analyses revealed that CYP-mediated metabolism was more strongly inhibited by ABT in the intestine (Fg) than in the liver (Fh). These results were consistent with those obtained using the conventional method in which oral and intravenous administration studies were performed using different rat groups. Therefore, the isotope-IV method is effective for performing PK analyses including DDIs after the oral administration of drugs.